Extinguishing Mining License C and Its Impact on Community Development - Dudung Hidayat; Junaedi Junaedi; Deni Yusup Permana; Gusti Yosi Andri; Karmenita Karmenita; Evelyn Azaria Valentina; Adhinda Maharani Rahardjo (Publikasi Indonesia, 2023)
Mining is an activity that is one of the biggest sources of regional income, but on the other hand mining activities often cause bad symptoms in the community. The existence of excavation c which causes environmental damage and loss to the surrounding community is a problem that never subsides for discussion. This study aims to identify and describe IUP Excavation C and its Impact on Community Development. This study uses a descriptive qualitative approach. The concept of legislation and spatial planning that has not been ideally actualized has resulted in this phenomenon not being handled properly, especially in the Cirebon and surrounding areas, even though there is already a legal basis and concept of environmental management but it seems as if it already exists. not yet realized.